3D study on the performance of cooling technique composed of heat spreader and microchannels for cooling the solar cells. (15th August 2018) - Soliman, Aly M.A.; Hassan, Hamdy
Highlights: New cooling technique of PV composed of microchannels (MC) and heat spreader (HS) is presented. The cooling performance of the different configurations of the MC and HS are studied. Using HS with MC increases PV efficiencies, net power and its life compared with system without HS. At CR = 20, using HS increases the cell efficiency by 50% and 53% at Re 5 and 65 respectively. At CR = 20, using HS increases the net power by 3.7% and 2.8% at Re 5 and 65 respectively. Abstract: The performance of a new cooling technique composed of a heat spreader (HS) and microchannels for cooling the solar cells (photovoltaic panels) is carried out. 3D steady state physical model for the solar cell coupled with the heat spreader and the microchannels is developed and solved numerically. The model is used to investigate the effect of using the microchannels with the HS on the performance of the solar cell. Also, the effect of different configurations of the microchannels-HS cooling system on the solar cell performance is studied. These configurations are tested at different concentration ratios (CRs) of the incident solar radiation and different Reynolds number ( Re ) of the coolant water inside the microchannels. The results indicate that the cooling system with HS has the smallest value of the solar cell temperature and the maximum temperature difference of the cell. It also has the greatest cell efficiency and output electrical and net power of the cell compared to the cooling system without HS. When the microchannels and the solar cell have equal surface area and their area is smaller than HS area, the solar cell has the maximum net power output at high Reynolds number. At low CR (CR = 5), the cooling system with HS increases the cell efficiency and the net power compared to the system without HS by about 8%, and 13% respectively at Re equal 5 and 13% and 2% respectively at Re equal 65. Also, at high CR (CR = 20), using HS increases the cell efficiency and the net power by about 50% and 3.7% respectively at Re equal 5, and 53% and 2.8% respectively at Re equal 65. At high Re number, the most efficient cooling system configuration occurs when the microchannels and the solar cell have the same area and the HS area is greater than their surface area.